Strategy Of The School Principle In Implementing The Semester Credit System (Sks) At Sma Tunas Luhur Paiton - Durratus Shaimah; Vastha Vusvitha (Pesantren Reviews, 2023)
The purpose of this study is to determine the planning steps the principal took in implementing the Semester Credit System at Tunas Luhur High School. How to implement the Semester Credit System at Tunas Luhur High School. To find out the learning outcomes of implementing the Semester Credit System at Tunas Luhur High School. The research method used in this research is qualitative research with a case study research design, which means that the researcher becomes an essential instrument in conducting this research. Researchers collected data from various primary and secondary data relevant to the research theme. The data collection stage was conducted using interview, observation, and documentation techniques. The results of this study were in the form of planning and implementation strategies carried out by the Principal of SMA Tunas Luhur Paiton. As for student learning outcomes in implementing the Semester Credit System at Tunas Luhur High School, it is pretty good, but there needs to be an in-depth evaluation, especially in paying attention to the child's development rate every month by running the Academic Refresh Program and providing motivation and providing additional classes to complete material that is both review and educational. Enrichment.